2018
DOI: 10.3390/app8030467
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Identification and Quantification Errors in Spectral CT Material Decomposition

Abstract: Material decomposition methods are used to identify and quantify multiple tissue components in spectral CT but there is no published method to quantify the misidentification of materials. This paper describes a new method for assessing misidentification and mis-quantification in spectral CT. We scanned a phantom containing gadolinium (1, 2, 4, 8 mg/mL), hydroxyapatite (54.3, 211.7, 808.5 mg/mL), water and vegetable oil using a MARS spectral scanner equipped with a poly-energetic X-ray source operated at 118 kV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…Multi‐energy spectral photon‐counting CT (SPCCT) is a novel imaging technique which uses a standard polychromatic x‐ray source and photon‐counting detector that records the number and energy of transmitted photons in multiple energy bins (), providing a range of energy‐dependent Hounsfield units (). As x‐ray attenuation of each material is energy dependent, multi‐energy bin data allow specific identification and quantification of several materials simultaneously (). Our previous findings show that multi‐energy SPCCT can differentiate MSU, CPP, and HA in vitro ().…”
Section: Introductionmentioning
confidence: 99%
“…Multi‐energy spectral photon‐counting CT (SPCCT) is a novel imaging technique which uses a standard polychromatic x‐ray source and photon‐counting detector that records the number and energy of transmitted photons in multiple energy bins (), providing a range of energy‐dependent Hounsfield units (). As x‐ray attenuation of each material is energy dependent, multi‐energy bin data allow specific identification and quantification of several materials simultaneously (). Our previous findings show that multi‐energy SPCCT can differentiate MSU, CPP, and HA in vitro ().…”
Section: Introductionmentioning
confidence: 99%
“…During the course of data analysis, we observed hidden K-edge phenomenon [50], which could be associated with low concentrations of AuNPs uptake by Raji and SKBR3; no enhancement of attenuation in energy bin 4 (Figures 2(c) and 2(d)) [50, 51]. However, our material decomposition algorithm [50] was able to recover this hidden information using the effective linear attenuation for each material (for each concentration and energy bin), which was estimated by taking the mean of respective regions in the reconstructed data, and demonstrates the uniqueness of spectral CT imaging [20].…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of the reconstructed images involved measuring the linear attenuation for each material and converting linear attenuation into Hounsfield units (HU). Using an in-house programme that uses the calculated effective mass attenuation of the calibration vials [20, 39], material decomposition (MD) was applied to the energy images and quantification of the trastuzumab and rituximab was performed by measuring the amount of gold in the cell clumps.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Afterwards, Si-Mohamed Salim et al further demonstrated that spectral CT has the capability of splitting two blended heavy metal-based contrast agents by qualitative and quantitative analysis in K-edge imaging [23]. Aamir Younis Raja et al proposed the MARS MD algorithm quantifying material identification at multiple material concentrations by switching reconstructed energy bins into sparse material images [24]. As a result, spectral CT has already gained constant attention due to its capacity of tissue characterization, damage or lesion detection, and material decomposition.…”
Section: Introductionmentioning
confidence: 99%